2016
DOI: 10.2989/16085906.2016.1179652
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary medical male circumcision for HIV prevention in fishing communities in Uganda: the influence of local beliefs and practice

Abstract: Local beliefs and practices about voluntary medical male circumcision (VMMC) may influence uptake and effectiveness. Data were gathered through interviews with 40 people from four ethnically mixed fishing communities in Uganda. Some men believed that wound healing could be promoted by contact with vaginal fluids while sex with non-regular partners could chase away spirits - practices which encouraged unsafe sexual practices. Information given by providers stressed that VMMC did not afford complete protection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…This should be a consideration for programme implementers because beliefs of this kind could put some newly circumcised men that adhere to them, as well as their sexual partners at the risk of HIV infection. This belief has also been reported among fishing communities on lake Victoria, Uganda [14,22] and in unpublished work in eastern Uganda [23]. It is also loosely mentioned in a national supervision report for HIV/AIDs activities [24], which may indicate that it is not only limited to this study.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This should be a consideration for programme implementers because beliefs of this kind could put some newly circumcised men that adhere to them, as well as their sexual partners at the risk of HIV infection. This belief has also been reported among fishing communities on lake Victoria, Uganda [14,22] and in unpublished work in eastern Uganda [23]. It is also loosely mentioned in a national supervision report for HIV/AIDs activities [24], which may indicate that it is not only limited to this study.…”
Section: Discussionsupporting
confidence: 74%
“…Such fears have also been reported by community members in a study in Tanzania [31]. Another reported belief related to healing was that vaginal fluids accelerate wound healing, which has also been reported in other areas of Uganda recently [14,22,23]. No man in this study reported engaging in early sex resumption for this purpose, but such misconceptions should not be ignored in SMC promotion messages to the general public.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Most recent data from a baseline sero-survey in 2014 from 12 fishing communities across Lake Victoria in Uganda found that SMC uptake among adults in fishing communities at baseline was between 41% and 66% (higher than 21% reported in Rakai fishing community) [46]. However, recent findings from a qualitative study on the uptake of SMC in our own study area point to continued barriers to uptake of SMC which need to be addressed if coverage is to increase [46]. While ART coverage in many fishing communities remains low (Rakai 13% in men vs 18% in women) or unknown [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative therefore that campaign strategists include in their messages such males who could lack a motivator to circumcise because they practice safe sex by emphasizing other benefits of VMMC such as improved sexual performance, hygiene and prevention of STIs among other benefits. Most respondents at 78.7% were in agreement that if one practiced unsafe sex they needed to undertake VMMC with 65.1% strongly agreeing and 13.7% simply agreeing (Table 2) According to (Mbonye, Kuteesa, Seeley, Levin, Weiss, & Kamali, 2016) VMMC in a number of African countries is being scaled up as a means to provide partial HIV protection which could be a reason why most respondents would vouch for VMMC especially where they engaged in unsafe sex. Communication messages need to clearly outline that undertaking VMMC doesn't guarantee complete protection against HIV/AIDS and other sexually transmitted diseases.…”
Section: Methodsmentioning
confidence: 99%